Measuring Customer Satisfaction: The Impact of Price, Food Quality, and Service in the Culinary Industry - Oktomi Harja (Journal of Economic Perspectives and Business Innovation, 2024)
AbstractCustomer satisfaction is a crucial determinant of competitiveness and long-term success in the culinary industry. This study investigates the impact of price perception, food quality, and service quality on customer satisfaction. Using a quantitative research approach, data were collected from customers of culinary businesses through structured questionnaires and analyzed using statistical methods to determine the relationship between variables. The results reveal that food quality has the strongest influence on customer satisfaction, followed by service quality and price fairness. Customers tend to value consistent taste, presentation, and hygiene, while responsive and friendly service enhances their overall dining experience. Although price remains an important consideration, customers are willing to pay more when they perceive high value in food and service. The study concludes that culinary businesses must maintain a balanced strategy that integrates competitive pricing, superior food quality, and excellent service to sustain customer loyalty and business growth. Keywords: customer satisfaction, price perception, food quality, service quality, culinary industry